Karakteristik Mutu Kimia Masker Wajah Beras Putih (Oryza sativa)-Lo’i Monca Tradisional Dompu - Kamagi, Tri Wahyudi N; Tanggasari, Devi (Department of Pharmacy, Bumigora University, 2022)
People in Dompu Regency West Nusa Tenggara have always used traditional face mask products, namely masks lo'i monca which protect facial skin from the sun when they are active all day outdoors. Dompu traditional masks (lo'i monca) are made from rice, tamarind shoots, bangle, curcuma, temugiring, and galangal. The purpose of this study was to determine the chemical quality of facial masks in lo'i monca terms of pH, water content and antioxidants. This type of research is a type of laboratory experimental research. Based on the results of laboratory tests, the average pH value obtained by the face mask powder preparation lo'i monca is 7.08. In testing the water content, the average value of the powder mask preparation lo'i monca was 13.3%. The results of the IC50 antioxidant activity test for powder mask preparations lo'i monca were 14.47 ppm. The results of laboratory tests that meet the requirements are pH levels because the pH value is in the range of 4.5-8.0, while the results on the water content do not meet the SNI requirements because the water content value is more than 10%, and the results of the antioxidant activity test the IC50 value of mask preparations.powder is lo'i monca classified as a very strong antioxidant because it is at an IC50 value of less than 50 ppm.